Risks and benefits of timely screw removal after thoracolumbar spine fractures treated with non-fusion technique. (July 2021) - Han, Moon-Soo; Lee, Gwang-Jun; Lee, Seul-Kee; Jang, Jae-Won; Moon, Bong Ju; Lee, Jung-Kil; Lee, Shin-Seok
Highlights: When fracture consolidation is confirmed, pedicle screws are no longer essential, but clear indications for screw removal following fracture consolidation have not been established. For clinicians planning to remove screws, we recommend screw removal be performed within 12 months for restoration of segmental motion angle after confirmation of fracture consolidation. When considering treatment strategies for TLSFs with CA ≥ 20°, a clinician should consider other surgical options such as long segment fixation and anterior reconstruction or posterolateral fusion, rather than screw removal after percutaneous-SSSF without fusion. Screw removal can be recommended for single level TLSFs with low severity vertebra body fracture (CA < 20°) after percutaneous-SSSF without fusion. Screw removal appears to be a safe and effective surgery for single-level low-severity vertebra body fractures following treatment using percutaneous-SSSF without fusion. Abstract: Background: Percutaneous-short segment screw fixation (SSSF) without bone fusion has proven to be a safe and effective modality for thoracolumbar spine fractures (TLSFs). When fracture consolidation is confirmed, pedicle screws are no longer essential, but clear indications for screw removal following fracture consolidation have not been established. Methods: In total, we enrolled 31 patients with TLSFs who underwent screw removal following treatment using percutaneous-SSSF without fusion. Plain radiographs, taken at different intervals, measured local kyphosis using Cobb' angle (CA), vertebra body height (VBH), and the segmental motion angle (SMA). A visual analogue scale (VAS) and the Oswestry disability index (ODI) were applied pre-screw removal and at the last follow-up. Results: The overall mean CA deteriorated by 1.58° (p < 0.05) and the overall mean VBH decreased by 0.52 mm (p = 0.001). SMA preservation was achieved in 18 patients (58.1%) and kyphotic recurrence occurred in 4 patients (12.9%). SMA preservation was statistically significant in patients who underwent screw removal within 12 months following the primary operation (p = 0.002). Kyphotic recurrence occurred in patients with a CA ≥ 20° at injury (p < 0.001) with a median interval of 16.5 months after screw removal. No patients reported worsening pain or an increased ODI score after screw removal. Conclusion: Screw removal within 12 months can be recommended for restoration of SMA with improvement in clinical outcomes. Although, TLSFs with CA ≥ 20° at the time of injury can help to predict kyphotic recurrence after screw removal, the clinical outcomes are less relevant.